Comparative effects of cumulus cell co-culture and conditioned medium on in vitro maturation of murine oocytes - Losman, Nik Abd Rahman Fahmi; Abdul Razak, Redzuan Nul Hakim; Md Isa, Muhammad Lokman; Mazlan, Muhammad Alif (Veterinary Research Institute, 2025)
Assisted reproductive technology plays a vital role in fertility treatment and conservation efforts, with in vitro maturation being a key technique in oocyte development. Cumulus cell co-culture and supplementation with cumulus cell co-culture secretions have been studied for their effects on in vitro maturation outcomes. In this study, mice were used as the animal model to evaluate the impact of these approaches on oocyte morphology and grading. The results showed that oocytes matured in the cumulus cell co-culture system had better zona pellucida integrity (54.2%) and a higher rate of polar body formation (70.8%) compared to those supplemented with cumulus cell co-culture secretions, where all oocytes showed zona pellucida abnormalities and only 30.0% exhibited normal polar body formation (p<0.05). Oocyte grading revealed a higher percentage of Grade A oocytes in the cumulus cell co-culture group (54.2%), whereas 70.0% of oocytes in the secretion supplementation group were classified as Grade C (p<0.05). These findings highlight the advantages of cumulus cell co-culture in improving oocyte quality and refining in vitro maturation protocols for reproduction and conservation biology.